Sustainable business growth: exploring operations decision-making - Schwab, Leila; Gold, Stefan; Reiner, Gerald (My University, 2017)
Purpose: The objective of this paper is to explore how operations decision-making may keep the growing firms within the boundaries of corporate and societal sustainability. Design/methodology/approach: We classify operations decisions during growth periods according to the three dimensions of the triple bottom line (economic, social and environmental). By means of a longitudinal case study of a family-owned wood construction firm that is in a process of intense growth, we identify, visually represent and analyse the complex sequences of selected managerial operations decisions. Findings: Our empirical data suggests that operations decisions made by managers during growth periods follow specific patterns. From our analysis, we derive various research propositions that investigate how a well-understood and therefore efficient and effective decision-making process can facilitate sustainable business growth. Research limitations/implications: Our findings offer opportunities for future studies to zoom in on specific parts of the decision-making process during growth periods. Moreover, given the exploratory nature of our study, future research should test hypotheses derived from our research propositions. Practical implications: This study investigates operations decision-making during growth, which is crucial for guiding companies through this complex transition phase. Originality/value: This conceptual and empirical analysis explores new theory and contributes to the vastly under-researched subject of sustainable business growth.
Keywords: Business growth; sustainability; decision-making; small and medium-sized companies; SMEs; longitudinal case study; family business